AUTOINFLAMMATORY DISEASES IN CHILDREN(The Lecture from 18th of September 2013, Conference «Topical Problems of Diagnostics and Treatment of Juvenile Rheumatoid Arthritis» (18–20 of September, 2013, St. Petersburg)) - M. Gattorno (Вопросы современной педиатрии)
Data about clinical signs, diagnostics and treatment of hereditary autoinflammatory syndromes, e.g. cryopyrin-associated periodic syndrome (CAPS), familial Mediterranean fever (FMF), TNF-receptor associated periodic syndrome (TRAPS-syndrome), hyperimmunoglobulinemia D syndrome (HIDS), Pyogenic Sterile Arthritis, Pyoderma Gangrenosum and Acne (PAPA) syndrome, juvenile sarcoidosis (Blau-syndrome) are shown in the article. These diseases are typically genetic disease with autosomal dominant and autosomal recessive type of inheritance. All diseases have common pathogenic features, such as spontaneous activation of innate immunity, maintaining of uncontrolled inflammation, absence of auto-antibodies and antigen-specific T-lymphocytes, over-secretion of interleukin-1 and good response to anti-interleukin-1 treatment. In this article you can see the basis of pathogenesis of the diseases, which determine the choice of treatment modalities and diagnostic algorhythms. Differences between clinical phenotypes of cryopyrin-associated periodic syndrome, such as familial cold urticaria (FCAS), Muckle-Wells syndrome and CINCA / NOMID syndrome are described thoroughly. You can find information about the whole group of periodic fevers and their differentiation. Data about international project «EuroFever» which can facilitate international collaboration in the fields of periodic fever are available.